SCREENING OF COMMON SIDDHA FORMULATIONS FOR ANTIMICROBIAL ACTIVITY AGAINST RESPIRATORY PATHOGENS - K, RAJALAKSHMI (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: The objective of this study was to screen the antimicrobial potential and minimal inhibitory concentrations (MICs) of selected commonly used Siddha formulations against respiratory pathogens. Methods: The most frequently and clinically used Siddha formulations for respiratory infections, namely Gowri chinthamani (R1), Sivanar amirtham (R2), Poorana chandrodayam (R3), Thalaga parpam (R4), Pavala parpam (R5), and Vasantha kusumasura mathirai (R6) were screened for antimicrobial activity against microbial type culture collection strains of Neisseria mucosa, Klebsiella pneumonia, Streptococcus pneumonia, Staphylococcus aureus, Pseudomonas aeruginosa, and Aspergillus niger, respectively, by agar well diffusion method. Tetracycline and fluconozole were used as positive control for bacterial and fungal pathogens, respectively. The zone of inhibition and the MICs were determined. Results: Among these formulations, Sivanar amirtham (R2) and Pavala parpam (R5) showed microbial sensitivity against all the above tested respiratory pathogens. The drug Sivanar amirtham (R2) showed higher zone of inhibition when compared to the control tetracycline. Conclusion: The study, therefore, supports the clinical claims of Siddha formulations to have potent antimicrobial activity and offer profound therapeutic benefits in respiratory infections. Keywords: Siddha, Sivanaramirtham, Pavala parpam, Antibacterial activity, Antifungal activity, Respiratory infections.